Systemic risk and sovereign debt in the Euro area - Deyan Radev (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
We introduce a new measure of systemic risk, the change in the conditional joint probability of default, which assesses the effects of the interdependence in the financial system on the general default risk of sovereign debtors. We apply our measure to examine the fragility of the European financial system during the ongoing sovereign debt crisis. Our analysis documents an increase in systemic risk contributions in the euro area during the post-Lehman global recession and especially after the beginning of the euro area sovereign debt crisis. We also find a considerable potential for cascade effects from small to large euro area sovereigns. When we investigate the effect of sovereign default on the European Union banking system, we find that bigger banks, banks with riskier activities, with poor asset quality, and funding and liquidity constraints tend to be more vulnerable to a sovereign default. Surprisingly, an increase in leverage does not seem to influence systemic vulnerability.
Keywords: C16; C61; G01; G21; 330; Sovereign debt; Sovereign default; Financial distress; Systemic risk; Contagion; Banking stability; Tail risk